2016
DOI: 10.1007/s00404-016-4104-z
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of the impact of Aurora A, Aurora B, Repp86, CDK1, CDK2 and Ki67 expression in two of the most relevant gynaecological tumor entities

Abstract: The prognostic value of the expression of Ki67 is overtrumped by alternative cell cycle kinases when it comes to prediction of axillary tumor spread and a shortened DFS, which might allow a further risk stratification in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…A German study performed in 93 ovarian benign and malignant tumour samples, showed hat the expression of AURKA, and AURKB among other cell cycle markers, were not predictive and were not associated with prognostic factors. 46 These results are in line with a second study 47 in 160 patients with primary EOC in which any AURKA immunostaining (score 1-3) was not predictive of impaired survival vs absence of expression (p=0.63).…”
Section: Aurk and Prognosis In Ocsupporting
confidence: 88%
“…A German study performed in 93 ovarian benign and malignant tumour samples, showed hat the expression of AURKA, and AURKB among other cell cycle markers, were not predictive and were not associated with prognostic factors. 46 These results are in line with a second study 47 in 160 patients with primary EOC in which any AURKA immunostaining (score 1-3) was not predictive of impaired survival vs absence of expression (p=0.63).…”
Section: Aurk and Prognosis In Ocsupporting
confidence: 88%
“…Cyclin-dependent kinase 1 (CDK1) plays an important role in the transition from G2 to M phase during the cell cycle [ 21 , 22 ], and multiple studies have verified that CDK1 acts as an oncogene. Indeed, CDK1 overexpression has been demonstrated in various tumors, including melanoma [ 23 ], pancreatic cancer [ 24 ], colon cancer [ 25 , 26 ], and mammary carcinoma [ 27 , 28 ]. In addition, some of these studies have shown that high CDK1 expression may be associated with poor prognosis in these malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The best would be, if those loci could use to predict the effectivity of drugs. Resistance to platinumbased chemotherapy is a significant clinical problem since patients with acquired resistance show a poor outcome in OvCa [14]. Developing a predictive tool to separate patients with platinum-resistant vs. platinum-sensitive tumours would be of potential advantage to disease management.…”
Section: Discussionmentioning
confidence: 99%